Assessing Safety Net Readiness in Response to Food Price Volatility - Grosh, Margaret; Andrews, Colin; Quintana, Rodrigo; Rodriguez-Alas, Claudia (World Bank, Washington, DC, 2017)
In 2008, when food prices rose precipitously to record highs, international attention and local policy in many countries focused on safety nets as part of the response. Now that food prices are high again, the issue of appropriate responses is again on the policy agenda. This note sets out a framework for making quick, qualitative assessments of how well countries' safety nets prepare them for a rapid policy response to rising food prices should the situation warrant. The framework is applied using data from spring 2011, presenting a snap?shot analysis of what is a dynamically changing situation. Based on this data safety net readiness is assessed in 13 vulnerable countries based on the following criteria: the presence of safety net programs, program coverage, administrative capacity, and to a lesser degree, targeting effectiveness. It is argued that these criteria will remain the same throughout time, even if the sample countries affected will be expected to vary. Based on this analysis the note highlights that though a number of countries are more prepared than they were in 2008, there is still a significant medium term agenda on safety net preparedness in the face of crisis. In this context, strategic lessons from the 2008 food crisis response are presented to better understand the response options and challenges facing governments and policy makers. The note concludes by calling for continued investment and scale up of safety nets to mitigate poverty impacts and help prevent long term setbacks in nutrition and poverty.